2016
DOI: 10.1063/1.4959557
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting radiative deep-level transitions in CuGaSe2 by photoluminescence

Abstract: Recent defect calculations suggest that the open circuit voltage of CuGaSe2 solar cells can be limited by deep intrinsic electron traps by GaCu antisites and their complexes with Cu-vacancies. To gain experimental evidence, two radiative defect transitions at 1.10 eV and 1.24 eV are characterized by steady-state photoluminescence on epitaxial-grown CuGaSe2 thin films. Cu-rich samples are studied, since they show highest crystal quality, exciton luminescence, and no potential fluctuations. Variations of the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Pohl et al calculated that In Cu in CuGaSe 2 is a much shallower donor than Ga In , suggesting that only Ga In can act as a detrimental recombination center in wide‐gap absorbers . In fact, the presence of intrinsic Ga Cu donor defect was experimentally confirmed in CuGaSe 2 by low‐temperature photoluminescence studies . On the other hand, Hanna et al found that the density of a deep acceptor in the absorber bulk is the lowest for samples with GGI ≈ 0.26, which also exhibit the lowest V OC losses, while its density increases monotonously for higher GGI values, resulting in V OC saturation .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pohl et al calculated that In Cu in CuGaSe 2 is a much shallower donor than Ga In , suggesting that only Ga In can act as a detrimental recombination center in wide‐gap absorbers . In fact, the presence of intrinsic Ga Cu donor defect was experimentally confirmed in CuGaSe 2 by low‐temperature photoluminescence studies . On the other hand, Hanna et al found that the density of a deep acceptor in the absorber bulk is the lowest for samples with GGI ≈ 0.26, which also exhibit the lowest V OC losses, while its density increases monotonously for higher GGI values, resulting in V OC saturation .…”
Section: Introductionmentioning
confidence: 97%
“…12 In fact, the presence of intrinsic Ga Cu donor defect was experimentally confirmed in CuGaSe 2 by low-temperature photoluminescence studies. 13,14 On the other hand, Hanna et al found that the density of a deep acceptor in the absorber bulk is the lowest for samples with GGI ≈ 0.26, which also exhibit the lowest V OC losses, while its density increases monotonously for higher GGI values, resulting in V OC saturation. 15,16 An alternative explanation for the observed V OC vs E g trend is an increased grain boundary recombination due to Cu-enrichment in grain boundaries (ie, no hole repulsion) for Ga-rich compositions.…”
mentioning
confidence: 99%
“…Recently similar deep level emission, DDA2 has been reported by Spindler et al around 1.1 eV in PL spectrum of a epitaxially grown CuGaSe 2 thin film. 20) Optical transition was explained with a shallow acceptor level around 100 meV above E V and deeper donor-level <530 meV below E C . As location of the deep level associated with this DL emission is close to the mid-gap position in CuGaSe 2 in this study, it might work as an active recombination center, i.e., nonradiative recombination of minority carrier electrons trapped at the level, E C − 630 meV may be possible with holes at E V .…”
Section: Deep Level Emission DLmentioning
confidence: 99%
“…It was only recently understood that this difference is not in the first place due to a difference in interface properties, but to bulk properties of Cu(In,Ga)Se 2 : in pure CuInSe 2 the quasiFermi level splitting, which is a measure of the opencircuit voltage an absorber could achieve, is higher in Cu-rich material than in Cu-poor [70,71], whereas in Cu(In,Ga)Se 2 (with Ga) the quasi-Fermi level splitting is lower in Cu-rich material than in Cu-poor, already in the absorber without any interface [72]. It has been proposed that the difference is due to a deep Ga Cu antisite defect [73,74], which forms a less detrimental pair with copper vacancies in Cu-poor material.…”
Section: Ultrathin Cellsmentioning
confidence: 99%